Pengembangan Modul Ajar Berbasis STEM Untuk Mewujudkan Kreativitas Pada Siswa Fase B Sekolah Dasar - Elsa Eri Asmara; Siti Patonah; Sukamto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The STEM approach to learning can be applied in teaching modules, which will later be implemented in learning in elementary schools. STEM involves natural science, engineering, technology, and mathematics as a basic reference in the development of Science and Technology (IPTEK) which requires students to innovate which demands a process of creativity from students. The purpose of the study is to produce STEM-based science teaching modules for grade IV students at SDN Kalisidi 03 Semarang Regency that are valid, practical, and effective in realizing student creativity. The type of research used is Research and Development (R&D) development research using ADDIE model development. This research place was carried out at Kalisidi State Elementary School 03 Semarang Regency in grade IV. Validation of teaching modules after being processed using the Aiken index gets a score of 0.96%, namely with a high category, effective teaching modules get a score of learning one before 72% and learning two by 91% by being declared effective and practical 97% of teaching modules get scores with very practical categories. So researchers hope that the teaching module developed can be used well for educators in Indonesia.